Enhancing Spirituality through Da’wah-Based Training: “Spiritual Motherhood “Class For Muslims Women in Indonesia - Uswatusolihah, Uus; Asmaya, Enung; Fuad, Muskinul (Journal of Posthumanism, 2025)
The spirituality of urban Muslim communities is increasingly receiving attention amidst social, economic, and cultural changes. In the fast-paced dynamics of modern life, many individuals, especially middle-class Muslims, seek ways to strengthen their spiritual values to balance worldly and religious aspects. This study explores the Spiritual Motherhood Training program in Jakarta, known as Da’wah-Based Training (DBT). Using a phenomenological approach, data was gathered through observations and purposive interviews with various informants. The analysis was conducted based on da’wah elements. Findings reveal that the Spiritual Motherhood training is designed for urban Muslim women, integrating modern self-development management with Islamic values. This program serves as a da’wah model that enhances the spirituality of middle-class women. It employs a combination of affirmations, visualizations, and emotional engagement, resulting in a profound impact on participants. The training fosters acceptance, surrender, and a deep belief in Allah’s power, which in turn inspires motivation and enthusiasm for success. As such, the Spiritual Motherhood training represents an innovative approach to da’wah for middle-class Muslim women.